PERJALANAN PENDIDIKAN SISTEM GANDA SEJAK MASA ORDE BARU SAMPAI AWAL REFORMASI (1994-2004) - Choiriyah Fitriyani; Nurzengky Ibrahim; Umasih Umasih (Jurnal Pendidikan Sejarah Indonesia, 2021)
Scientific and technological mastery form one of the essential elements for the development support of an advanced and self-sufficient nation. In the face of the challenges of development, it is hoped that science and technology will improve the quality of human resources so that communities are adequately qualified to adapt to each development. In an effort to improve the quality of human resources, governments have contributed to the efforts of improving the quality of the vocational high school (SMK). Vocational secondary schools play a key role in preparing learners to create graduates who have a professional attitude at work to prepare for a competent workforce. As a dual system of education (PSG) in vocational high schools began a new partnership between schools and the unprecedented business world. Involvement between the two sides is one of the key factors in the success of the dual system education. The school has a responsibility to make the work world a guide in the making of a curriculum or a study in a school. This is to match the compatibility between the compatibility of the workplace skills of the educational society and the types of work the industry/job needs. Thus, institutions of education are required to be able to produce graduates who have the skills to work according to the types of work that the work world or industry needs. While the industry is expected to be able to guide learners in industrial practice activities, planning all the needs needed by learners during carrying out PSG.